Segregation of municipal solid waste and recycling potential for residential hostel in Uitm Sarawak / Lydia Dundun Francis, Juplin Kinti and Nurdiana Wakimin - Francis, Lydia Dundun; Kinti, Juplin; Wakimin, Nurdiana (Research Management Institute (RMI), 2012)
Effective waste management through municipal solid waste (MSW) composition studies is important for numerous reasons, including the need to estimate material recovery potential, to identify sources of component generation, to facilitate design of processing equipment, to estimate physical, chemical, and thermal properties of the waste and to maintain compliance with Malaysian Environmental Quality Act1974. The scope of this study focuses on the segregation of municipal solid waste (MSW) in the residential college in Universiti Teknologi Mara Samarahan (UiTMCS) as there is no data regarding on the amount of waste being generated daily. An important point for the success of a waste management plan is the need for accurate and up to data on the quality and quantity of the waste that is generated in the area. With this data, proper management strategies can be planned by top management of UiTMCS and put into action, notwithstanding the fact that this data could also be used to predict the future trends in the quantity and quality of the MSW of the residential college in UiTMCS. This study will be carried out to have a comprehensive characteristic of the waste that is generated and to determine MSW composition and generation rate. Hand sorting will be used for classifying the collected wastes into the following categories: plastics, paper, metals, aluminium, leather-wood-textiles-rubbers, organic wastes, non-combustibles and miscellaneous according to ASTM D 5231 - 92 : Standard Test Method for the Determination of the Composition of Unprocessed Municipal Solid Waste. The sorting procedure of Municipal Solid Waste (MSW) in this study will be carried out according to the spot sampling method. Based on this method used by Kathirvale et al. (2003), about 30 to 50 kg of mixed wastes is to be taken which is then sorted. The MSW are sorted according to their categories such as plastics, polystyrene pack, organic or food waste, papers, glasses, ceramic, textiles, rubbers, metals and others are found in the MSW. Further analysis included proximate analysis for moisture content of combustible materials. The laboratory analysis is carried out on the MSW samples are based on recommendations from the American Society of Testing and Material (ASTM). Result from this study will provide data to categorize the MSW in UiTMCS and the current trends is study and by means of a prediction model for the future trend is predicted and proposed the appropriate method to treat it.